2006
DOI: 10.1242/jcs.03229
|View full text |Cite
|
Sign up to set email alerts
|

Glutaredoxins Grx3 and Grx4 regulate nuclear localisation of Aft1 and the oxidative stress response inSaccharomyces cerevisiae

Abstract: Grx3 and Grx4, two monothiol glutaredoxins of Saccharomyces cerevisiae, regulate Aft1 nuclear localisation. We provide evidence of a negative regulation of Aft1 activity by Grx3 and Grx4. The Grx domain of both proteins played an important role in Aft1 translocation to the cytoplasm. This function was not, however, dependent on the availability of iron. Here we demonstrate that Grx3, Grx4 and Aft1 interact each other both in vivo and in vitro, which suggests the existence of a functional protein complex. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
267
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(288 citation statements)
references
References 51 publications
13
267
8
Order By: Relevance
“…The current view is that Aft1 continuously shuttles between the cytosol and the nucleus but that specific signals maintain it in a given compartment. For instance, it was shown that its translocation from the nucleus to the cytoplasm is promoted by an iron-dependent multimerization and that Grx3/4 are essential for the nuclear export of Aft1 upon-iron replete conditions (52,53). Importantly, the recognition of Aft1 involves at least a negatively charged region in the yeast Grx4 formed by the last 16 C-terminal residues (supplemental Fig.…”
Section: Rieske-type [2fe-2s] Coordination Occurs In Grx-bola_hmentioning
confidence: 99%
“…The current view is that Aft1 continuously shuttles between the cytosol and the nucleus but that specific signals maintain it in a given compartment. For instance, it was shown that its translocation from the nucleus to the cytoplasm is promoted by an iron-dependent multimerization and that Grx3/4 are essential for the nuclear export of Aft1 upon-iron replete conditions (52,53). Importantly, the recognition of Aft1 involves at least a negatively charged region in the yeast Grx4 formed by the last 16 C-terminal residues (supplemental Fig.…”
Section: Rieske-type [2fe-2s] Coordination Occurs In Grx-bola_hmentioning
confidence: 99%
“…The Grx3-type monothiol glutaredoxins have a modular structure that consists of an N -terminal thioredoxin domain and C-terminal glutaredoxin domains. Budding yeast cells contain two Grx3-type monothiol glutaredoxins, Grx3 and Grx4, which are expressed at similar levels, are 63% identical, and appear to be functionally equivalent (31)(32)(33). Mammals express a single Grx3-type glutaredoxin, which contains two C-terminal glutaredoxin domains in addition to the N-terminal thioredoxin domain.…”
Section: Monothiol Glutaredoxinsmentioning
confidence: 99%
“…Grx3/4 and Fra2 are required for iron sensing by the major iron-dependent transcription factor in budding yeast, Aft1 (31,32,36). Under iron-deficient conditions, Aft1 activates the transcription of genes involved in the response to iron deficiency (37).…”
Section: Monothiol Glutaredoxinsmentioning
confidence: 99%
“…The absence of both proteins makes the cells sensitive to hydrogen peroxide. In the absence of both Grx3 and Grx4 there is a constitutive oxidative stress induced, in part, by the deregulation of iron homeostasis (Pujol-Carrion et al, 2006). There are some other reports demonstrating similar regulations of other protein kinases.…”
Section: Ros Detoxifier Proteins Acting As Signalling Regulatory Molementioning
confidence: 93%
“…Grx3 and Grx4 are two putative glutaredoxins but there have not been described any enzymatic property related to that putative function. They are involved in the regulation of Aft1 a transcription factor required for the correct iron homeostasis (Pujol-Carrion et al, 2006;Ojeda et al, 2006). Grx4 is required for the maintenance of cable structure.…”
Section: Ros Detoxifier Proteins Acting As Signalling Regulatory Molementioning
confidence: 99%